2020
DOI: 10.3390/sports8040041
|View full text |Cite
|
Sign up to set email alerts
|

Are Blood Pressure and Cardiovascular Stress Greater in Isometric or in Dynamic Resistance Exercise?

Abstract: Medical and sports medicine associations are reluctant to endorse isometric exercise to the same extent as dynamic resistance exercise (RE). The major concern is the fear of greater increases in blood pressure (BP) that might be associated with isometric exercise. This review comprehensively presents all human studies that directly compared the magnitude of hemodynamic responses between isometric and dynamic RE. We also discuss possible mechanisms controlling BP-response and cardiovascular adjustments during b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 74 publications
(202 reference statements)
2
20
0
Order By: Relevance
“…In contrast, previous studies had evaluated isometric one-handed handgrip exercise protocols with a broad range of exercise duration, handgrip application, and devices hampering a general comparability (19,(23)(24)(25). However, several comparative studies investigated the differences between dynamic and isometric (static) handgrip exercise (26)(27)(28)(29). Although most authors found no significant differences in hemodynamic response, Stebbins et al observed a significantly higher increase of heart rate, blood pressure, and cardiac output with increasing handgrip strengths compared with isometric handgrip protocols.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, previous studies had evaluated isometric one-handed handgrip exercise protocols with a broad range of exercise duration, handgrip application, and devices hampering a general comparability (19,(23)(24)(25). However, several comparative studies investigated the differences between dynamic and isometric (static) handgrip exercise (26)(27)(28)(29). Although most authors found no significant differences in hemodynamic response, Stebbins et al observed a significantly higher increase of heart rate, blood pressure, and cardiac output with increasing handgrip strengths compared with isometric handgrip protocols.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, previous studies had evaluated isometric one-handed handgrip exercise protocols with a broad range of exercise duration, handgrip application and devices hampering a general comparability [19,[22][23][24]. However, several comparative studies investigated the differences between dynamic and isometric (static) handgrip exercise [25][26][27][28]. Although most authors found no signi cant differences in hemodynamic response, Stebbins et al observed a signi cantly higher increase of heart rate, blood pressure and cardiac output with increasing handgrip strengths compared to isometric handgrip protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Due to concerns regarding adverse events caused by excessive cardiovascular stress, e.g., blood pressure (BP), the application of IEs and PEs has been constrained despite the strengths and benefits [ 2 , 6 ]. Over 330 million people were diagnosed with CVDs in China, and over 245 million were hypertensive [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Only small-muscle (handgrip), short-duration (2 min per set), and intermittent IEs were recommended in the hypertensive population [ 4 ]. IEs in larger muscles and with longer durations were considered to exhibit a more pronounced increase in cardiovascular and metabolic stress [ 6 ], which may be another cause of the limited application of large-muscle IEs or the lack of studies in which IEs were continuously performed to exhaustion. As the repetition maximum in isotonic exercise, the maximum duration of IE is essential to evaluate the relative intensity and exercise volume for prescribing effective and individualized training programs [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation